METHODOLOGY FOR IDENTIFYING GLOBAL AND NATIONAL SYSTEMICALLY IMPORTANT BANKS AND ITS THEORETICAL FOUNDATIONS - Ashurov Jaloliddin Eshpulatovich (Scholars Digest Publishing, 2024)
The article theoretically studies the activities of systemically important banks. In particular, the opinions and scientific research of economists on this issue are studied. At the same time, the main emphasis is placed on the methodology for identifying global and national systemically important banks. In particular, the experience and analytical data of the USA, Germany, Great Britain, and Japan are studied.
Keywords: commercial bank, systemically important banks, global systemically important banks, national systemically important banks, assessment indicators, Basel Committee.